Generating iPS Cells from MEFS through Forced Expression of Sox-2, Oct-4, c-Myc, and Klf4 - Welstead, G. Grant (MyJove Corporation, 2008)
Pluripotency can be induced in differentiated murine by viral transduction of Oct4, Sox2, Klf4, and c-Myc (Takahashi and Yamanaka, 2006; Wernig, et al., 2007; Okita, et al., 2007; Maherali, et al., 2007). We have devised a reprogramming strategy in which these four transcription factors are expressed from doxycycline (dox)-inducible lentiviral vectors (Brambrink et al., 2008). Using these inducible constructs, we can derive induced pluripotent stem (iPS) cells from mouse embryonic fibroblasts (MEFs). In this video, we demonstrate the procedure for the generation of inducible lentiviruses that express the four transcription factors and show how to infect MEFs with these viruses in order to produce iPS cells. By using inducible lentiviruses, the expression of the four factors in controlled by the addition of doxycyline to the culture medium. The advantage of this system over the traditional retroviral infection is the ability to turn the genes on and off so that the kinetics of reprogramming and gene expression requirements can be analyzed in detail.